Jamu as a Preventive Health Solution: Community Service by DPC ASPETRI Ngawi at Maospati Terminal in Commemoration of Eid al-Fitr 1446 H - Wibowo, Teguh Setiawan; Zakaria, Musliadi; Oktavianis, Heni (Westscience Press, 2025)
Jamu, a traditional Indonesian herbal concoction, offers numerous health benefits and has been used for generations as a natural means of maintaining physical well-being. In welcoming Eid al-Fitr 1446 H, the DPC ASPETRI Ngawi organized a community service activity at Maospati Terminal with the aim of introducing jamu as an alternative preventive health solution. This activity included educational outreach about the benefits of jamu and the distribution of free herbal drinks to terminal visitors. The initiative is expected not only to raise public awareness about the importance of natural health preservation but also to reintroduce jamu as a part of cultural heritage applicable in daily life. The program aims to promote a healthy lifestyle rooted in local wisdom, while preserving the relevance of jamu as a traditional health solution to this day.